PELAKSANAAN PENGADAAN BARANG/JASA PEMERINTAH DITINJAU DARI PERPRES NOMOR 16 TAHUN 2018 TENTANG PENGADAAN BARANG/JASA PEMERINTAH DI KANTOR PERTANAHAN KOTA BANDAR LAMPUNG - Aryana Wisastra; baharudin; Indah Satria (Law Faculty of Universitas Bandar Lampung, 2019)
Indonesia began to regulate the procurement of goods/services electronically from the government since 2010. This is indicated by the appointed Presidential regulation number 54 year 2010 as amended by Presidential Regulation No. 4 year 2015, then amended again to be presidential Regulation No. 16 year 2018 on procurement of goods/services Government. The problem that will be discussed is how the implementation of goods procurement/Government services are reviewed from the Presidential Decree No. 16 of 2018 at the Land Office of Bandar Lampung, what are the inhibitory factors in the implementation of the procurement of goods/services in the Office Land of Bandar Lampung. The research methods used are normative and empirical juridical, using secondary and primary data. Results of the research from the implementation of goods procurement/Government Services reviewed from Presidential Decree No. 16 of 2018 in the Land office of Bandar Lampung now has referred to the Presidential Decree No. 16 of 2018, the inhibitory factor in the implementation of goods /services in the Land office of Bandar Lampung City, among others, lack of human resources that have a certificate of expertise, network/servers that are frequent disruptions and difficult when creating the approximate price yourself.